Analisis Pemikiran Al-Ghazali Tentang Keadilan Distribusi Kekayaan Untuk Mengatasi Ketimpangan Ekonomi Di Era Modern - Salma fauziah; Lina Marlina (4, 2026)
The issue of wealth distribution will be an important topic for serious discussion in the field of economics today. Although globalization and technological advances have driven economic growth, this has often not been accompanied by a fair and equitable distribution of prosperity in society. In Islamic thought, Imam al-Ghazali put forward the principle of economic justice that prioritizes harmony between personal and common interests. This study aims to examine al-Ghazali's views on wealth distribution and evaluate its potential in overcoming economic inequality in the modern era.. This study uses quantitative methods, namely methods sourced from journals, books, articles, and related data, by exploring al-Ghazali's thoughts from his classical works, as well as those discussing the application of wealth distribution within the framework of Islamic economics. The findings reveal that al-Ghazali emphasized the need to distribute wealth through sharia mechanisms such as zakat, infaq, and sadaqah, and prohibited economic practices that are harmful and detrimental to society, so that wealth is not concentrated in the hands of a minority group. These ideas are still very relevant as a foundation for designing economic policies that are fair and support social welfare. Thus, al-Ghazali's concept can serve as an alternative solution to modern economic inequality by strengthening ethical values and equalizing economic access for society. Abstrak Masalah distribusi kekayaan Akan menjadi topik yang penting untuk pembahasan serius di bidang ekonomi saat ini. Meskipun globalisasi dan kemajuan teknologi mendorong kemajuan pertumbuhan ekonomi , hal tersebut sering kali tidak diiringi dengan pembagian kesejahteraan yang adil dan merata di masyarakat. Di dalam pemikiran Islam, Imam al-Ghazali mengemukakan prinsip keadilan ekonomi yang mengutamakan harmoni antara kepentingan pribadi dan kepentingan bersama. penelitian ini bertujuan untuk menelaah bagaimana pandangan al-Ghazali tentang distribusi kekayaan serta mengevaluasi potensinya dalam mengatasi persoalan ketimpangan ekonomi di era modern . penelitian ini menggunakan metode kuantatif yaitu metode yang bersumber dari jurnal,buku,artikel dan data terkait , dengan menggali pemikiran al-Ghazali dari karya-karyanya yang klasik ,serta yang membahas penerapan distribusi kekayaan dalam kerangka ekonomi Islam . Temuan kajian mengungkapkan bahwa al-Ghazali menegaskan perlunya pengaliran harta melalui mekanisme syariah seperti zakat, infak, sedekah, dan larangan terhadap praktik ekonomi yang membahayakan dan merugikan masyarakat, agar kekayaan tidak terpusat pada kelompok minoritas saja. pemikiran tersebut masih sangat berlaku sebagai fondasi untuk merancang kebijakan ekonomi yang adil dan mendukung kesejahteraan sosial. Dengan demikian, konsep al-Ghazali dapat berfungsi sebagai alternatif penyelesaian dalam menghadapi masalah ketimpangan ekonomi modern, melalui penguatan nilai-nilai etis dan pemerataan akses ekonomi bagi masyarakat.